Non‐Gaussian statistics of CO‐OFDM signals after non‐linear optical fibre transmission. Issue 3 (1st June 2018) - Kashef, Seyed Sadra; Azmi, Paeiz; Bosco, Gabriella; Matinfar, Mehdi D.; Pilori, Dario
Abstract : In this study, the statistical distribution of the received signal in a coherent optical orthogonal frequency‐division multiplexing (CO‐OFDM) system with quadrature‐phase shift keying modulation in the orthogonal frequency‐division multiplexing (OFDM) subcarriers is investigated, and the accuracy and correctness of the Gaussian probability density function (pdf) assumption is analysed. The well‐known Anderson–Darling test is utilised to measure the deviation extent of the statistical distribution of the received signal from the Gaussian pdf. Finally, the Johnson S U ‐distribution is suggested as a more exact distribution for the statistical modelling of the received signal. After non‐linear propagation, its accuracy is assessed through comparison with Monte‐Carlo simulations, based on the time‐domain split‐step Fourier method.